Pelaksanaan Pembinaan Terhadap Narapidana Resiko Tinggi (Percobaan Bunuh Diri) di Lembaga Pemasyarakatan Perempuan Klas IIB Jambi - Gani, Ruslan Abdul; Ibrahim, Ibrahim; Safitri, Wulan Sari (Universitas Batanghari Jambi, 2023)
Jambi Class IIB Women's Penitentiary, which is a special prison for women, during training, one prisoner was found to have attempted suicide, this is a high risk prisoner. The aim of this research is to understand and analyze the implementation of coaching, obstacles and efforts towards high risk convicts (attempting suicide) at the Class IIB Women's Penitentiary in Jambi. The research method uses sociological juridical. Implementation of Guidance for High Risk Prisoners (Suicide Attempts) at the Class IIB Jambi Women's Penitentiary undergoes the same coaching program as other inmates, but the coaching is carried out with extra monitoring, especially on the use of tools so that they are prohibited from taking part in gardening activities and are further directed towards dancing activities. , singing, vocal processing which leads to healing and mental development of the prisoner. Obstacles encountered in the Implementation of Guidance for High Risk Prisoners (Suicide Attempts) at the Class IIB Jambi Women's Penitentiary, namely the legal factor itself (changes in correctional law thereby changing policies in the guidance of prisoners), law enforcement factors (the absence of psychologists and the absence of specifically for mental training coaches), infrastructure factors (the absence of special infrastructure for these prisoners), community factors (the family's indifference in healing the mental health of these prisoners) and cultural factors (society's stigma towards former prisoners in society. Efforts made in Overcoming obstacles in the Implementation of Guidance for High Risk Prisoners (Suicide Attempts) at the Jambi Class IIB Women's Penitentiary, namely making policy adjustments, socializing the existence of correctional institutions to prisoners, collaborating with the community, prisoners' families in healing the mental health of these high risk prisoners. Suggestions put forward are the need for the existence of a trainer with psychologist education at the Class IIB Jambi Women's Correctional Institution, increasing the socialization of the existence of the correctional institution in providing guidance for prisoners to form independence, personality and skills to return to society and collaboration with mental hospitals in developing prisoners' mental health.